Understanding Construction Contractors’ Intention to Undertake Consummate Performance Behaviors in Construction Projects - Ling Yan; Liang Guo; Yan Ning (Advances in Civil Engineering)
Contractors’ consummate performance behavior (CPB) refers to that contractors perform within the spirit of the contract. This is important to improve project performance. However, few studies have investigated why contractors would undertake CPB. Drawing on the theory of planned behavior (TPB), this study aims to examine which factors influence the intention of CPB. To achieve this, a questionnaire survey was undertaken in China, with 195 valid questionnaires from project managers and contract managers being received. Data were analyzed through structural equation modeling and fuzzy set qualitative comparative analysis. The results show that the intention of CPB is mainly influenced by attitude toward benefit/cooperation/social value, subjective norm, and perceived behavioral control. Attitude toward social value has the greatest impact on the intention of CPB, whereas the subjective norm is least effective on the intention of CPB. In addition, three equifinal combinations result in the intention of CPB. Attitude toward cooperation and subjective norm are the core of the contractors’ intention of CPB. These two factors cannot be replaced by other factors.